Snille piker går ikke til Sydpolen - Arnesen, Liv (Damm, 1995)
Keywords: Antarktis; Sydpolen; ekspedisjoner; polarekspedisjoner; reiseskildringer

Norges polare interesser - Berg, Roald (Norge på egen hånd, 1995)
Keywords: Antarktis; Norge; historie; polarområdene; utenrikspolitikk

Using multiple data sources to enhance photogrammetry for mapping Antarctic terrain - Fox, Adrian J (Polar Research, 1995)
Keywords: Antarktis; flyfoto; geografi; kartlegging; luftfoto; satellittbilder

Cato mot Sydpolen - Hauge, Odd Harald; Bry, Knut; Ebbesen, Lars (Pax, 1995)
Keywords: Antarktis; Nordmenn; Sydpolen; ekspedisjoner; fotokunst; funksjonshemmede; oppdagelsesreiser; polarekspedisjoner; reiser; reiseskildringer

Immune responses during an antarctic summer - Lugg, Desmond J.; Ursin, Holger; Donovan, Kevin; Konrad Muller, H.; Quinn, Dennis (Pathology, 1995)
The immune status of 29 members of the Australian National Antarctic Research Expeditions (ANARE) was investigated before, during, and after a 56 day summer voyage to Antarctica and correlated with psychological and physiological parameters. All subjects were healthy. Expedition personnel demonstrated decreased cell mediated immune responses (CMI) assessed by the CMI Multi-test; 21% were hypoergic. The major associated observation was a significant negative correlation with anxiety in Antarctica. However, perceived anxiety was greater before and after the voyage. No significant changes were found in T and B lymphocyte subsets, immunoglobulin and complement components and cutaneous blood flow, nor was there any clinical evidence of illness. Of the hormones examined only cortisol was low predeparture which may reflect increased perceived anxiety at that time. Changes in immune control mechanism were apparent as shown by reduced CMI responses and lowered tetanus antibody levels. Stress factors are postulated to induce depression of the immune response in Antarctica. The association with anxiety suggests that brain peptides or associated cytokines may have a role in mediating these immune events. Such alterations in immune status have implications for health management in isolated and extreme conditions.
Keywords: Antarktis; fysiologi; immunologi; psykologi

Forskrift om vern av miljøet i Antarktis - Miljøverndepartementet (1995)
Publisher: Lovdata Place: Oslo
Keywords: Antarktis; jus; miljøvern

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans and Coplanar Biphenyls in Antarctic Fur Seal Blubber - Oehme, Michael; Schlabach, Martin; Boyd, Ian (Ambio, 1995)
Levels of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) as well as of coplanar (non-ortho substituted) polychlorinated biphenyls (CB-77, CB-126 and CB-169) have been determined in 11 fur-seal blubber samples from female Antarctic fur seals. Measurable PCDD/PCDF concentrations averaging 2 ppt TEQ (Nordic model) were found. This is considerably less than in Arctic seals. In addition, the PCDD/PCDF congener patterns differed between Antarctic and Arctic seals. The levels of CB-77, CB-126 and CB-169 (8.5-41 pg g-1 for single congeners in average) in Antarctic fur seals were also much lower than in Arctic ringed and harp seals. A possible explanation of these differences is the overall lower environmental pollution of the Southern Hemisphere, though an influence of different age and sex distributions cannot be excluded. The data passed all quality assurance criteria that had been established for such low levels.
Publisher: [Springer, Royal Swedish Academy of Sciences]
Keywords: Antarktis; forurensning; marin biologi; miljøgifter; pinnipedier; polarområdene; seler

Invertebrates in Hot and Cold Arid Environments - Sømme, Lauritz (Springer-Verlag, 1995)
Keywords: Antarktis; forskning; kuldetoleranse; virvelløse dyr